The COREL grammar: a conceptual representation language - Periñán-Pascual, Carlos; Mairal-Usón, Ricardo (Onomázein, 2010)
Natural language understanding systems require a knowledge base provided with conceptual representations reflecting the structure of human beings’ cognitive system. Although surface semantics can be sufficient in some other systems, the construction of a robust knowledge base guarantees its reuse in most natural language processing applications. In this scenario, FunGramKB is presented as a multipurpose knowledge base whose model has been particularly designed for natural language understanding tasks. Indeed, one of the features which has remarkably contributed to the success of this knowledge base is the expressive power of its notational system. The aim of this paper is to describe the grammar, together with its theoretical foundation, of the conceptual representation language used in FunGramKB.